Nutritional supplementation and oxidative stress: Implications for physical activity and sport - Petry, E.; Alvarenga, M.; Cruzat, Vinicius; Toledo, J. (Colegio Brasileiro de Ciencias do Esporte, 2013)
Physical exercises associated with a balanced diet are important factors for health promotion. However intense and prolonged or strenuous exercise may promote chronic infam-mation, overtraining and increased susceptibility to infections. Being cause or consequence, one of the factors that contribute to deleterious effects is exacerbated increase in the synthesis of pro-oxidant compounds, known as reactive oxygen species (ROS) and nitrogen species (RNS). The increase of ROS and RNS may reduce the body antioxidant capability, a condition known as oxidative stress. Oxidative stress has been implicated as a promoter of injuries to various cellular constituents, especially on the membranes, an effect known as lipid peroxidation. To attenuate the effects of ROS and RNS, the body has the antioxidant defense system, located in different cellular compartments and with different functions. Studies have increasingly shown that the antioxidant system can be infuenced by specific nutritional interventions, among which are included vitamins, minerals, favonoids and amino acids. Considering the fact that thousands of people engage in the practice of physical exercise every day, and that many of them go beyond their limits, this review aims to address the major sites of synthesis of ROS during exercise and nutrition strategies and their possible mechanisms action on the antioxidant defense system.